Grammaticalization and parametric variation - Batllori, Montse; Hernanz Carbó, María Luisa; Picallo, M. Carme; Roca, Francesc (Oxford University Press, UK, 2005)
In this outstanding collection of new work the methods and theories of formal syntax are focussed on grammatical variation and change. The editors open the volume with an extensive and accessible introduction to the ideas and techniques deployed in the book and the phenomena and issues on which they are brought to bear. Seventeen chapters follow, divided into two parts, the first concerned with grammaticalization and the second with parametric variation. These show what the. application of contemporary theories of syntax and language variation can reveal about syntactic change and variation an.